Gender and Human Rights Within UNESCO's International Heritage Discourse: An Analysis of the World Heritage and Intangible Heritage Conventions. (2nd September 2021) - Whittington, Vanessa
ABSTRACT: Human rights discourses have significant relevance to contemporary understandings of heritage and its conservation, particularly in the context of the key international conventions for safeguarding the world's cultural heritage promulgated by UNESCO. The right to heritage is recognized as a human right falling under the right to culture or cultural identity. However, states are the primary bodies responsible for heritage identification and conservation, and may prefer to preserve the heritage of dominant social groups. Heritage identification and management by states, including the nomination of items for inclusion on the World Heritage List of the Convention Concerning the Protection of the World Cultural and Natural Heritage and the Representative List of the Convention for Safeguarding the Intangible Cultural Heritage, thus has the potential to compromise the cultural rights of marginalized social groups, including women. Existing research and original research discussed herein reveal a dearth of heritage associated with women on both Lists. However, the problematic gender dynamics of this discourse goes beyond simple representativeness to encompass the ways in which women and their heritage are portrayed. The Representative List typically seeks to maintain existing social relations, including gender relations, with negative implications for women's human rights set out in the UN Convention to Eliminate all Forms of Discrimination Against Women .